Spatial Characteristics and Influence of Topography and Synoptic Systems on PM2.5 in the Eastern Monsoon Region of China - Shengli Zhu; Zhaowen Wang; Kai Qu; Jun Xu; Ji Zhang; Haiyi Yang; Wenxin Wang; Xiao Sui; Min Wei; Houfeng Liu (Aerosol and Air Quality Research)
Abstract Based on the PM2.5 concentration in the autumn and winter of 2015–2019, the characteristics of urban air pollution in the eastern monsoon region of China were discussed. The spatial distribution and interregional influence of fine particle pollution under different synoptic weather and topography in the eastern monsoon region of China were illustrated. According to synoptic systems, regional PM2.5 pollution episodes were classified into three categories, including Uniform Pressure field (UP, 60.00%), Pre-High Pressure (PreHP, 30.91%) and Inverted-Trough (IT, 9.09%). The K-Means algorithm combined with the HYSPLIT backward trajectory clustering analysis indicated four clusters under UP controlled, and under weak pressure field was responsible for the elevation of PM2.5 concentration, where the Beijing-Tianjin-Hebei and its surrounding areas were the most polluted region. For PreHP, four clusters eased after cold front. For IT, three clusters were ascertained, and the severe PM2.5 pollution area was in the central and southern of the North China Plain. This study provided a scientific basis for the joint prevention of PM2.5 pollution based on topographic and meteorological characteristics in Eastern China.